The Role of Islamic Education on Gen Z's Emotional Problems: Critical Analysis in a Humanistic Approach - Azfar, Fani; Yudela, Farida Wardah; Fikri, Muhammad 'Alimul; Ifana, Siti Rohmatin Nur; Sopyani, Pipi (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
Generation Z is a group that grows in the digital era with various, social and technological intensive dynamics.​ The impact of an all-around environment is fast and always connected, often causing​ pressure and significant emotions, such as anxiety, depression, and crisis identity. Emotional problems become a big challenge in the form of psychological welfare. Islamic education is rooted in the teachings of the Koran and Sunnah runway spiritual and moral values that can contribute positively to the health and emotions of Gen Z. This article aims to know How Islamic education can play a role in overcoming the problem of Gen Z's emotions through a humanistic approach. Study this uses a method to study literature or a library. Source of data in research This is obtained from various sources like journal scientific, book, report research, and related documents. Research results show that Islamic education has potential when integrated in a way appropriate to the approach. Helping Gen Z manage his emotions can also build a strong and balanced character.​ However, reaching Maximum effectiveness requires​ integration with an approach relevant to modern psychology in a contemporary context.